Decision Analysis of Airbrake Midterm Production Planning at the Machining Department, PT 'X' Bandung - Yudoko, Gatot; Diaz, lqsan (SBM ITB, 2009)
PT 'X' Bandung is a state-owned companies and one of its products is vehicle. One of the important subassemblies of the vehicle is the airbrake. This paper is aimed finding and selecting feasible midterm production plan alternatives for the Machining Department for the production of air brake for the upcoming scheduled three consecutive periods, namely period 1 (12 days), period 2 (12 days), and period 3 (27 days) using decision-making methodology base on Hayes et al., consisting of evaluating the existing capacity to meet orders, defining alternatives for meeting those likely orders, performing financial analysis of each alternative, assessing key criteria or key issues for each alternative, and selecting and defending the alternative to be pursued. We calculated that the existing capacity was insufficient to meet the orders, and therefore,we developed four alternatives. The first alternative was trying to meet the demand using the available resources by accepting the lateness in which penalty costs would have to be calculated based on the contract agreement. The second alternative was adding capacity through overtime and in this regard the overtime costs would be calculated. The Thrid alternative was adding capacity by purchasing new machines in which capital required would be calculated. And the last alternative was a mix of overtime and the addition of new machines and the related costs would be calculated as well. The alternative with the least cost would be selected. Based on our analysis using two criteria, namely compliance to schedule and costs, we conclude that the last alternative is the best production plan for the company in meeting the demand of airbrake for the upcoming three periods.Keywords:Â midterm production planning, decision making methodology, airbrake